Inside Back Cover: A Critical Review on Hemicellulose Pyrolysis (Energy Technol. 1/2017). Issue 1 (2nd August 2016) - Zhou, Xiaowei; Li, Wenjun; Mabon, Ross; Broadbelt, Linda J.
Abstract : Biomass pyrolysis—a sustainable way to produce renewable fuels and chemicals : The cover image depicts a sustainable world where green fuels and chemicals will be produced from renewable, abundant, and cheap biomass by using a variety of technologies (e.g., biological, thermochemical, and catalytic). Hemicellulose, one of the three major components of biomass, receives scarce attention compared to cellulose and lignin; however, it deserves much more. Herein, this contribution highlights the progress in characterizing the composition and structural features of hemicellulose and particularly focuses on salient experimental investigations, reaction mechanisms, and kinetic modeling of hemicellulose pyrolysis through a critical literature analysis. Challenges and future prospects are also discussed. More details can be found in the Review by X. Zhou, W. Li, R. Mabon, L. J. Broadbelt from Northwestern University and Exxon Mobil (DOI: 10.1002/ente.201600327 ).